Landfills represent significant atmospheric sources of exposure to halogenated flame retardants for urban-adapted gulls. (February 2020) - Sorais, Manon; Mazerolle, Marc J.; Giroux, Jean-François; Verreault, Jonathan
Graphical abstract: Highlights: Halogenated flame retardants (HFRs) were quantified in passive air samplers in gull. Daily sampling rates in passive air samplers were highest for Penta and DecaBDE. Air was shown to be a significant exposure source for HFRs in urban-adapted gulls. Landfills were shown to represent important hotspots of exposure to HFRs in gulls. Abstract: Halogenated flame retardants (HFRs) are contaminants that are abundantly emitted from waste management facilities (WMFs) and that became ubiquitous in air of urbanized regions. Urban birds including gulls have adapted to exploiting human food resources (refuse) in WMFs, and have thus experienced population explosions worldwide. However, foraging in WMFs for birds may result in exposure to HFRs that have been shown to be toxic for animals. The objective of this study was to determine the influence of foraging near or in various WMFs on the atmospheric exposure of birds to HFRs, and to localize other sources of HFRs at the regional scale in a highly urbanized environment. We measured the atmospheric exposure to HFRs in one of the most abundant gull species in North America, the ring-billed gull ( Larus delawarensis ), breeding in the densely-populated Montreal area (Canada) using a novel approach combining bird-borne GPS dataloggers and miniature passive air samplers (PASs). We determined concentrations of 11 polybrominated diphenyl ethers (PBDEs) and three emerging HFRs of high environmental concern in PASs carried by gulls. We show that the daily sampling rates (pg/day) of PBDEs in PASs were highest in gulls foraging in or around landfills, but were not influenced by meteorological variables. In contrast, the daily sampling rates of emerging HFRs were lower compared to PBDEs and were not influenced by the presence of gulls in or near WMFs. This study demonstrates that atmospheric exposure to HFRs and perhaps other semi-volatile contaminants is underestimated, yet important for birds foraging in landfills.